1982
DOI: 10.1070/rc1982v051n06abeh002857
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of the Photolysis of Certain Hydrocarbons by Vacuum Ultraviolet Radiation

Abstract: A recurrent method for irreducible representation calculation of five-dimensional quasispin group SO(5)t is proposed. The explicit IRs in physical orthonormal basis with multiplicity 3 2>up to three, such as (2tt), (2t + 2t) and (It) when t = 1, §, 2, § are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 4 publications
(7 reference statements)
0
12
0
Order By: Relevance
“…Indeed, alpha-line of Lyman series of atomic hydrogen (121.6 nm; photon energy 10.7 eV) dominates in the spectrum of Solar VUV radiation. Moreover, radiation with wavelength 121.6 nm induces photoionization of macromolecules with their subsequent transformations similar to those induced by other types of ionizing radiations (Dorofeev & Skurat 1982;Barbashev et al 1992;Van Eesbeek et al 1994;Skurat et al 1997;Skurat et al 2001;Skurat & Samsonov 2001;Skurat 2003). However, a substantial difference of absorbed radiation doses is observed in gamma-radiolysis, bombardment by fast electrons and VUV irradiation (see, for example, (Skurat 2003)).…”
mentioning
confidence: 92%
“…Indeed, alpha-line of Lyman series of atomic hydrogen (121.6 nm; photon energy 10.7 eV) dominates in the spectrum of Solar VUV radiation. Moreover, radiation with wavelength 121.6 nm induces photoionization of macromolecules with their subsequent transformations similar to those induced by other types of ionizing radiations (Dorofeev & Skurat 1982;Barbashev et al 1992;Van Eesbeek et al 1994;Skurat et al 1997;Skurat et al 2001;Skurat & Samsonov 2001;Skurat 2003). However, a substantial difference of absorbed radiation doses is observed in gamma-radiolysis, bombardment by fast electrons and VUV irradiation (see, for example, (Skurat 2003)).…”
mentioning
confidence: 92%
“…This effect is usually referred to as standing wave effect or finite wavelength effect in the literature. [19][20][21][22] For example, Hebner et al performed diagnostics of single frequency operating in argon and driven at frequencies between 10 and 190 MHz. [22] They found that with grounded lower electrode the spatial distribution of argon ions transitioned from uniform to center peaked as the excitation frequency was increased on the upper electrode, as shown in Fig.…”
Section: Plasma Processing Tools In Microelectronics Fabricationmentioning
confidence: 99%
“…Skin effects usually develop with increasing power deposition or pressure and tends to enhance the power deposition near the electrode edges. [19][20][21][22] Another method of improving the performance of CCP sources is applying a transverse static magnetic field (tens to hundreds of Gauss) approximately parallel to the electrodes with the goal of either increasing the plasma density for a given pressure or lowering the operating pressure. In this configuration the devices are often called magnetically enhanced reactive ion etching (MERIE) reactors.…”
Section: Plasma Processing Tools In Microelectronics Fabricationmentioning
confidence: 99%
See 2 more Smart Citations